The Effect of Rubber Training on Gyaku-Tsuki Punching Speed in Karate Athletes - Oktavia, Nava; Denay, Naluri; Sari, Desi Purnama (International Martial Arts and Culture Journal, 2023)
Background and aim. Speed is one aspect of physical performance that reflects the muscle's ability to act quickly through cycles of contraction and relaxation. In karate, punching speed is essential for achieving points, particularly in the gyaku-tsuki chudan technique. This study aims to evaluate the effect of rubber training on gyaku-tsuki punch speed among karate practitioners.Methods This study used a descriptive research method. The sampling technique employed was total sampling, involving 12 karate athletes. Data were collected using the gyaku-tsuki punch speed test.Results.  The results indicate a significant effect of rubber training on gyaku-tsuki punch speed. The calculated t value was 7.05, which exceeds the t-table value of 1.83 at a significance level of α = 0.05 with degrees of freedom (df = 9).Conclusions. Rubber training has a significant impact on improving gyaku-tsuki punch speed among karate athletes